Influencia de las estrategias metodológicas interactivas para el planteamiento y resolución de problemas de razonamiento en la asignatura de matemáticas en los estudiantes de educación básica superior de la unidad educativa Amazonas en la ciudad de Machala, provincia de El Oro periodo 2014 - 2015. - Morocho Belduma, Dilma Teresa (2015)
This thesis began visiting Amazonas Education Unit with the aim of agreeing on the cooperation of the authorities of the institution, having earned this approach began doing theoretical research on the subject, which was quite difficult because there is a large development of interactive methodology, overcome this shortcoming was selected and made the development of relevant research tools.